Psychological characteristics of strong-willed qualities of athletes of team and individual sports - Julija N. Anisimova; Galina N. Kameneva; Gennady S. Prygin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Sports activity as one of many types of human activity is considered as a form of professional activity in which there is a professional formation and development of the personality with all signs inherent in it.The purpose of the study was to establish specific manifestations of volitional qualities in athletes of team and individual sports. The study used a systematic approach to the study of the properties of the personality, including the eight-component model, developed byA.I. Krupnov, where each property of the personality contains a cognitive, dynamic, setting-target, motivational, regulatory, emotional, evaluative and productive components. On the basis of this model features of such strong-willed qualities as persistence and organization at athletes of team and individual sports were revealed. As research methods used: bibliographic review of foreign and domestic psychological literature, testing, quantitative and qualitative analysis of empirical data.In particular, it was found that the perseverance of athletes in individual sports is manifested in the intentions of a personal nature, the desire to realize themselves, improve their financial situation, to be independent and independent. The persistence of team sports athletes is manifested in the desire to help others, in bringing the planned business to the end and in perseverance. As for organization, the athletes of individual sports is aimed more at the plant and interests of a personal nature, while the athletes of team sports with more focus on the interests of a public nature, they prefer order, often take the lead in organizing and preparing new cases, as well as carefully control and check themselves in the course of any work.